Secreted protein acidic and rich in cysteine (SPARC) induces apoptosis of human brain vascular smooth muscle cells through regulating HK2 in intracranial aneurysm - Zhou, Donglin; Li, Tao; Tan, Xianjun; Yun, Chenping; Jiang, Peng; Zhang, Tongfu; Kuang, Hong; Wang, Yunyan (Frontiers in Molecular Neuroscience, 2023)
Background Vascular smooth muscle cell (VSMC) dysfunction is one of the crucial pathologic processes in the development of intracranial aneurysm (IA). Secreted protein acidic and rich in cysteine (SPARC), a multifunctional glycoprotein, is overexpressed in many tumor, but its underlying mechanism in vascular disease has not been elucidated. The aim of this study is to evaluate the potential function of SPARC in IA generation and regulation of mitochondrial function in VSMC. Methods Human brain vascular smooth muscle cells were treated with recombinant SPARC to detect apoptosis-related markers. The downstream targets affecting mitochondrial dysfunction after SPARC treatment were explored by transcriptome sequencing and bioinformatics analysis, and verified using by immunohistochemistry and western blot. Further in vitro experiments verified the role of downstream targets in regulating VSMC mitochondrial function. Results Secreted protein acidic and rich in cysteine (SPARC) expression was associated with the risk of IA rupture. SPARC induces mitochondrial pathway apoptosis in human brain VSMC. We screened 40 differentially expressed genes related to mitochondrial function after SPARC treatment. Hexokinase 2 (HK2) was identified as a downstream target of mitochondrial pathway apoptosis in VSMC induced by SPARC. In addition, immunohistochemical results confirmed that the difference between SPARC and HK2 expression is located mainly in the smooth muscle layer of IA. Overexpression of HK2 reversed the SPARC-induced increase in apoptosis and mitochondrial damage in VSMC. Conclusion Secreted protein acidic and rich in cysteine (SPARC) regulated mitochondrial function in VSMC and induced apoptosis through HK2, which plays an important role in the formation and rupture of IA. Targeting SPARC may be a novel strategy to delay the development of intracranial aneurysms.